2011
DOI: 10.1002/eji.201141700
|View full text |Cite
|
Sign up to set email alerts
|

Intratumor OX40 stimulation inhibits IRF1 expression and IL‐10 production by Treg cells while enhancing CD40L expression by effector memory T cells

Abstract: Treg cells maintain the tumor microenvironment in an immunosuppressive state preventing an effective anti-tumor immune response. A possible strategy to overcome Treg-cell suppression focuses on OX40, a costimulatory molecule expressed constitutively by Treg cells while being induced in activated effector T cells. OX40 stimulation, by the agonist mAb OX86, inhibits Treg-cell suppression and boosts effector T-cell activation. Here we uncover the mechanisms underlying the therapeutic activity of OX86 treatment di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 66 publications
1
35
0
Order By: Relevance
“…Indeed, IRF-1 can directly bind to the Il10 promoter and induce IL-10 transcription in response to IFN-a [31]. In a mouse model of cancer, it has been demonstrated that tumorinfiltrating Treg locally release high amounts of IL-10, in line with high expression of IRF-1 [17]. Of note, the engagement of the OX40 receptor on Treg surface, an approach known to reduce the suppressive function of murine Treg, resulted in the downregulation of IRF-1 in vitro, and significantly reduced IL-10 release in vivo in tumor-infiltrating Treg [17].…”
Section: Ifn-regulated Genes and Tregmentioning
confidence: 94%
See 2 more Smart Citations
“…Indeed, IRF-1 can directly bind to the Il10 promoter and induce IL-10 transcription in response to IFN-a [31]. In a mouse model of cancer, it has been demonstrated that tumorinfiltrating Treg locally release high amounts of IL-10, in line with high expression of IRF-1 [17]. Of note, the engagement of the OX40 receptor on Treg surface, an approach known to reduce the suppressive function of murine Treg, resulted in the downregulation of IRF-1 in vitro, and significantly reduced IL-10 release in vivo in tumor-infiltrating Treg [17].…”
Section: Ifn-regulated Genes and Tregmentioning
confidence: 94%
“…In a mouse model of cancer, it has been demonstrated that tumorinfiltrating Treg locally release high amounts of IL-10, in line with high expression of IRF-1 [17]. Of note, the engagement of the OX40 receptor on Treg surface, an approach known to reduce the suppressive function of murine Treg, resulted in the downregulation of IRF-1 in vitro, and significantly reduced IL-10 release in vivo in tumor-infiltrating Treg [17]. These data indicate that IRF-1 may sustain IL-10 production in Treg, even though the impact of type-I IFNs in inducing such response in certain contexts, such as cancer, remains to be clarified.…”
Section: Ifn-regulated Genes and Tregmentioning
confidence: 94%
See 1 more Smart Citation
“…It is believed that one of the main advantages of targeting OX40 is the abrogation of Treg-mediated immunosuppression by inhibition of the activity of Treg cells (114) or by direct depletion of these cells (91,115,116). Thus, combination of anti-OX40 mAbs with cyclophosphamide (chemotherapy that is capable of partially depleting Treg cells) showed a synergistic effect in a poorly immunogenic B16 murine melanoma tumor and was associated with a reduction of Treg at the tumor site (111).…”
Section: Ox40 Costimulationmentioning
confidence: 94%
“…16 PE-Cy7 anti-CD4 (RM4–5), APC anti-Foxp3 (FJK-16s), PE anti-CD103 (2E7) and FITC anti-GITR were purchased from eBioscience. Surface staining was performed on cells obtained from each organ by incubating antibodies at 5 μg/mL on ice for 30 min in PBS containing 2% FBS.…”
Section: Methodsmentioning
confidence: 99%